2010
DOI: 10.3109/09513591003632043
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative baby take-home rate among women with PCOS treated by IVF

Abstract: Although the baby take-home rate was similar among women with PCOS, and controls, the outcomes of consecutive cycles were not equal. Cumulative data give more realistic information than pooled cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Some authors have suggested, though, that oocyte quality lags, resulting in lower implantation, and higher miscarriage rates as well as more aneuploidy [40,41]. Others reported no meaningful outcome differences between PCOS and control patients in IVF cycles [42,43]. Weghofer et al determined that, over all, PCOS patients produce larger euploid embryo numbers, yet still demonstrate lower pregnancy and higher miscarriage rates [44], suggestive of a non-chromosomal quality factor in oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested, though, that oocyte quality lags, resulting in lower implantation, and higher miscarriage rates as well as more aneuploidy [40,41]. Others reported no meaningful outcome differences between PCOS and control patients in IVF cycles [42,43]. Weghofer et al determined that, over all, PCOS patients produce larger euploid embryo numbers, yet still demonstrate lower pregnancy and higher miscarriage rates [44], suggestive of a non-chromosomal quality factor in oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Twelve studies reported this outcome (Dor et al, 1990;Kodama et al, 1995;Palep-Singh et al, 2007;Kuivasaari-Pirinen et al, 2010;Swanton et al, 2010;Mellembakken et al, 2011;Kalra et al, 2013;Okohue et al, 2013;Li et al, 2014;Chen et al, 2016;Shi et al, 2018;Hwang et al, 2016). After adjusting for multiple COH cycles, the pooled live birth rate per cycle was (6,465/18,539 (34.9%) in the PCOS group vs 9,315/30,778 (30.3%) in the non-PCOS group; pooled RR = 1.01 [0.89, 1.16]; I 2 = 82%) (Fig.…”
Section: Live Birth Rate (Lbr) Lbr Per Cyclementioning
confidence: 96%
“…A further five studies were awarded a star for similar age (Doldi et al, 1999;Weghofer et al, 2007;Tehrani Nejad et al, 2011;Chen et al, 2016;Shi et al, 2018;Hwang et al, 2016), and one study awarded a star for equivalent BMI (Melado Vidales et al, 2017). Loss to follow-up was reported in only 5 (Hardy et al, 1995;Kuivasaari-Pirinen et al, PCOS group does not meet Rotterdam criteria (Ashkenazi, 1995) Entire cohort already pregnant (Sterling, 2016) Same cohort as another study (Wan, 2015) Differing IVF protocols in PCOS and control group (Dor, 1990) One PCOS criterion used in control group (Kim, 2009) In-vitro maturation used (Le Chen et al, 2016;Shi et al, 2018;Hwang et al, 2016;Almasi-Hashiani et al, 2018) of the 21 studies. We were able to estimate the loss rate from the data provided in six other studies (Urman et al, 1992;Hardy et al, 1995;Weghofer et al, 2007;Mellembakken et al, 2011;Zhong et al, 2012;Li et al, 2014).…”
Section: Assessment Of Biasmentioning
confidence: 99%
See 2 more Smart Citations